Advance of Prussian Blue‐Derived Nanohybrids in Energy Storage: Current Status and Perspective. Issue 14 (5th January 2023) - Wang, Ronghao; Qian, Chengfei; Zhang, Zherui; Shen, Hao; Xia, Jingjie; Cui, Dingyu; Sun, Kaiwen; Liu, He; Guo, Cong; Yu, Feng; Li, Jingfa; Bao, Weizhai
Abstract: Great changes have occurred in the energy storage area in recent years as a result of rapid economic expansion. People have conducted substantial research on sustainable energy conversion and storage systems in order to mitigate the looming energy crisis. As a result, developing energy storage materials is critical. Materials with an open frame structure are known as Prussian blue analogs (PBAs). Anode materials for oxides, sulfides, selenides, phosphides, borides, and carbides have been extensively explored as anode materials in the field of energy conversion and storage in recent years. The advantages and disadvantages of oxides, sulfides, selenides, phosphides, borides, carbides, and other elements, as well as experimental methodologies and electrochemical properties, are discussed in this work. The findings reveal that employing oxides, sulfides, selenides, phosphides, borides, and other electrode materials to overcome the problems of low conductivity, excessive material loss, and low specific volume is ineffective. Therefore, this review intends to address the issues of diverse energy storage materials by combining multiple technologies to manufacture battery materials with low cost, large capacity, and extended service life. Abstract : Based on the advantages of Prussian blue analog and its derivatives, the advantages, experimental methods, and electrochemical characteristics of corresponding metal compounds are systematically summarized. This paper mainly introduces and analyzes the optimization and design of how to improve the conductivity, reduce the loss of active materials, and increase the specific capacity.